Quality Improvement of Tin Ingot Product Using Six Sigma Method at PT Timah Tbk - Idriwal Mayusda (OPSI, 2023)
Bangka brand (BA) tin metal bar (ingot) has the highest defect percentage value of 2.01% from June to September 2021. This percentage exceeds the minimum non-conformity product standard of 0.25 %. This study aims to identify the types and factors that cause defects and propose improvements for the quality of products. The research uses the six-sigma method with DMAIC stages. Types of ingot defects include winging, rough surface, curved edges, bumps on the surface, presence of flakes, asymmetrical brand logos, spatters of tin metal, cracks/breaks, and exceeding weight specification. The results of the sigma level are 2.36 (variable data) and 3.15 (attribute data). The highest RPN value (240) occurs in the type of failure of the tin ingot test with the cause of failure, namely, the machine is experiencing troubleshooting. The second highest RPN value (210) occurs in the casting process with the cause of failure, namely the operator's lack of job mastery. Proposed improvements that can be implemented are the application of tin casting process work instructions. The implementation results show an increase in the sigma level to 2.44 (variable data) and 3.19 (attribute data).